POLITICAL COMMUNICATION AND VOTER PARTICIPATION IN THE 2020 REGIONAL HEAD ELECTIONS IN BANGLI REGENCY - I Wayan Sedia; I Putu Gede Suwitha; I Nyoman Weda Kusuma; I Nengah Punia (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2024)
This research analyzes political communication in voter participation during the 2020 simultaneous regional head elections in Bangli Regency amidst the Covid-19 pandemic. It examines forms of political communication, underlying ideology, and implications. Using a qualitative approach, data were collected through in-depth interviews and document studies, applying theories such as persuasive communication, critical hegemony, social practice, and power-knowledge relations. Findings indicate that online political communication during the pandemic facilitated interaction between election actors and voters but had drawbacks. Issues included limited election information, outdated voter data, and inaccurate permanent voter lists. Additionally, budget constraints, insufficient personal protective equipment, and health protocol violations were significant challenges. The ideology behind political communication was the hegemony of community figures, political elites, and successful teams over voters, resulting in power-knowledge relations and transactional political practices. Elderly and disabled voters in mountainous areas were particularly marginalized. Practical findings show that online political communication limited voter references, reducing freedom in choosing candidates. Theoretical findings indicate that online political communication disrupts social interaction during Covid-19, and hegemony theory is effectively applied in the Bangli community, which practices local culture. However, power- knowledge relation theory cannot be universally applied, as traditional figures dominate voters and the central executive board determines coalitions and candidate pairs. Keywords: political communication, participation, regional elections, Bangli Regenc